Critical Analysis of India's Community Development Programme - Community Projects Administration, Planning Commission (Community Projects Administration, Planning Commission, Government of India, 1956)
The critical analysis of India’s Community Development Programme (CDP), notably examined by Carl C. Taylor, presents a balanced evaluation of its transformative aspirations and operational constraints within the broader framework of rural reconstruction. Conceived as a comprehensive response to entrenched rural poverty and socio-economic stagnation, the programme sought to integrate economic advancement with social, political, and cultural renewal through decentralized governance and participatory development. Emphasizing community empowerment, local leadership cultivation, and the harmonization of extension services, the CDP envisioned villages as foundational units of self-governance and development, closely linked with Panchayati Raj institutions. However, the analysis identifies significant challenges, including inadequate training of Village Level Workers, limited mobilization capacity, institutional fragmentation, over-reliance on governmental direction, and the insufficient functional preparedness of newly elected local leaders. The programme’s success is shown to depend on transforming administrative initiatives into genuine grassroots movements characterized by self-reliance, social cohesion, and inclusive participation—particularly of marginalized groups such as Scheduled Castes. Furthermore, the report underscores the necessity of integrating governmental agencies, fostering two-way communication channels between officials and villagers, respecting traditional socio-cultural dynamics, and instituting continuous qualitative and quantitative evaluation mechanisms. Ultimately, the study concludes that sustainable rural transformation in India requires a shift from top-down bureaucratic implementation to a community-driven model rooted in empowered local institutions, coordinated administrative support, and the cultivation of democratic participation at the village level.
Government of India Planning Commission
Keywords: Community Development Programme; Rural Empowerment; Panchayati Raj Institutions; Decentralized Governance; Local Leadership Development; Village Level Workers; Participatory Development; Institutional Integration; Social Cohesion; Scheduled Castes Inclusion; Administrative Reform; Grassroots Democracy